Competition law and the SMEs: does the Competition Act 2010 promote or hinder the development of the SMEs in Malaysia? - Abdul Rahman, Nasarudin; Ariff Abdul Ghadas, Zuhairah; Hassan, Halyani; Ahamat, Haniff (Kuala Lumpur, International Business, Economics and Law Conference, 2013)
The role of competition law is to protect the process of competition among firm in the market by prohibiting anti-competitive behaviours such as Cartel and abuse of dominant position. It provides a level playing field between firms to compete openly in the market. However, it is often argued that by promoting open competition, competition law gives large firms with large capital and resources and more advance technology a competitive advantage vis-à-vis small and medium firms. This forces the smaller firms out of the market due to the inability to compete with the larger competitors. This paper will analyze the legal provisions regulating competition in the market by virtue of the Competition Act 2010. This paper will then analyze to what extent the law promotes the interest of small and medium firms. This paper argues that the competition law protects rather than hinders the development of SMEs in Malaysia. For example, the provisions on dominant position and abuse thereof give the power to the competition commission to prevent large firms from taking advantage of their market power to the detriment of consumers and smaller firms. However, competition law should not be used to protect inefficient and weak competitors and should not punish larger firms just because they are more efficient than the smaller firms. The law only controls the conducts that affect the process of competition and the smaller firms may benefit naturally from this protection.